Improvements of a room-temperature magnetic refrigerator combined with Stirling cycle refrigeration effect. (July 2016) - Gao, X.Q.; Shen, J.; He, X.N.; Tang, C.C.; Li, K.; Dai, W.; Li, Z.X.; Jia, J.C.; Gong, M.Q.; Wu, J.F.
Highlights: A high pressure hybrid magnetic refrigerator combined with Stirling refrigeration was designed. A centric Halbach cylinder permanent magnet was used in the hybrid machine. An optimal phase angle of this hybrid system was figured out. The cooling powers improved by 28.5% in the hybrid machine. Abstract: A high pressure hybrid refrigerator that combines the active magnetic refrigeration effect with the Stirling cycle refrigeration effect at room temperature is studied here. In the apparatus, a helium-gas-filled alfa-type Stirling refrigerator uses Gd sheets as the regenerator and the regenerator is put in a magnetic field varying from 0 to 1.4 T, which is provided by a Halbach-type rotary permanent magnet assembly. With an operating pressure of 5.5 MPa and a frequency of 2.5 Hz, a no-load temperature of 273.8 K was reached in 9 minutes, which is lower than that of 277.6 K for pure Stirling cycle. For the hybrid operation, cooling powers of 40.3 W and 56.4 W were achieved over temperature spans of 15 K and 12 K, respectively. For the latter case, the cooling power improves by 28.5% if compared with that exploiting only the Stirling cycle refrigeration effect.